Answers

The Brainliest Answer!
2015-08-25T20:47:11+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
√3  Cos x  - Sin x = 1

divide the equation by 2:

=> √3/2  Cos x - 1/2  sin x = 1/2
=> Sin π/3 Cos x - Cos π/3 Sin x = Sin π/6
=> Sin (π/3 - x) = Sin π/6
=> Sin (x - π/3) = Sin (-π/6)  or Sin (π + π/6)

=>    x - π/3 =    2 n π - π/6  or  2 n π + 7 π/6
       x = 2 n π + π/6    or  2 n π + 3 π / 2

  
this 2 n π + 3 π/2 can also be expressed as:  2 n π + 2π - π/2
             ie.,  2 m π - π / 2

Hence, x = 2 n π + π/6    and x =  2 n π - π/2

==========================
another way:

√3 Cos x - Sin x = 1
=> √3/2 Cos x  - 1/2 Sin x = 1/2
=>  Cos π/6 Cos x - Sin π/6 Sin x = Cos π/3
=>  Cos (x + π/6)  = Cos π/3

     we have general solution for Cos X = Cos Y,  X = 2 n π + Y  or  2 n π  - Y
 
=>  x + π/6  =  2 n π  + π/3  or  2 n π - π/3
=>  x = 2 n π + π/6    or    2 n π - π/2



2 5 2
click on thanks button above please